Household Income, Food Insecurity and Nutritional Status of Migrant Workers in Klang Valley, Malaysia - Chan Foong Mei; Erwin Martinez Faller; Lau Xiao Chuan; Jacklyn San Gabriel (Ubiquity Press, 2020)
Background and Purpose: Food insecurity exists whenever accessibility to nutritious food is limited. It affects a person's health with regards to nutritional status, indicated by malnourishment or overnutrition. This study aims to study the relationship between household income, household food insecurity, and weight status of migrant workers in Klang Valley, Selangor. Method: A cross-sectional study involving a convenience sampling of 125 documented migrant workers from five selected countries was conducted. A researcher-administered questionnaire consisting of socio-demographic questions, three-day 24-hour dietary recall (3DR), and nine-item Household Food Insecurity Access Scale was used. Anthropometric measurements, including body weight, height, and waist circumference, were taken. Findings: About 57.6% of the households studied were food insecure (24.8% mildly, 29.6% moderately, and 3.2% severely). Burmese were found to have the highest rate of household food insecurity (96%). The majority of the migrant workers were of normal weight (68.0%). No significant relationship was found between monthly household income and household food security status ('p' = 0.475), as well as between household food security status and weight status ('p' = 0.535). Conclusion: Results imply that food security status affects certain nutrient intake among migrant workers. There were no significant associations between variables. Interventions focusing on nutritional education on food choices and implementation on health policy are recommended. Further studies should consider the accessibility, nutritional-related diseases, and dietary aspects of migrant workers, which are risk factors for food insecurity.